Pengaruh Environmental Knowledge dan Green Marketing Terhadap Green Consumer Behavior Pada Konsumen Fore di Kota Medan - Setiawan, Setiawan; Ester Cahyani Sianturi; Fatimah Zahra Tambunan; Olan Harafi Tampubolon; Onan Marakali Siregar; Ummi Salamah Sitorus (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study was conducted to explore the impact of Environmental Knowledge and Green Marketing on Green Consumer Behavior Fore coffee in the city of Medan. The methodology used was a quantitative approach with an associative research type. There were 100 respondents who became the research sample selected using purposive sampling. Data collection was carried out by distributing questionnaires online, and the data was then analyzed using SmartPLS to test the validity, reliability, and interaction between variables in the structural model. The results showed that the research instruments met the standards of validity and reliability. The main finding showed that Environmental Knowledge did not have a significant effect on Green Consumer Behavior, which means that consumers' environmental knowledge has not been able to encourage green consumption behavior in a tangible way. Conversely, Green Marketing has been proven to have a positive and significant effect on Green Consumer Behavior. This explains that green marketing strategies implemented by companies, such as environmentally friendly promotions, eco-labeling, and sustainability messages, are powerful factors that influence consumers' green consumption behavior. This study confirms that green marketing efforts play a greater role in shaping environmentally friendly consumer behavior than consumers' level of environmental knowledge. These findings have important implications for companies in designing more effective and sustainability-oriented marketing strategies.